Fulvalene as a platform for the synthesis of a dimetallic dysprosocenium single-molecule magnet. Issue 22 (26th May 2020) - He, Mian; Guo, Fu-Sheng; Tang, Jinkui; Mansikkamäki, Akseli; Layfield, Richard A.
Abstract : A series of fulvalene-supported dimetallic dysprosium metallocene SMMs provides a roadmap to poly-cationic dysprosocenium single-molecule magnets. Abstract : The dinucleating fulvalenyl ligand [1, 1′, 3, 3′-(C5 t Bu2 H2 )2 ] 2− (Fv tttt ) was used to synthesize the dimetallic dysprosocenium cation [{Dy(η 5 -Cp*)}2 (μ-BH4 )(η 5 :η 5 -Fv tttt )] + (3 ) as the salt of [B(C6 F5 )4 ] − (Cp* = C5 Me5 ). Compound [3 ][B(C6 F5 )4 ] was obtained using a method in which the double half-sandwich complex [{Dy(BH4 )2 (THF)}2 (Fv tttt )] (1 ) was reacted with KCp* to give the double metallocene [{Dy(Cp*)(μ-BH4 )}2 (Fv tttt )] (2 ), followed by removal of a bridging borohydride ligand upon addition of [(Et3 Si)2 (μ-H)][B(C6 F5 )4 ]. The dimetallic fulvalenyl complexes 1–3 give rise to single-molecule magnet (SMM) behaviour in zero applied field, with the effective energy barriers of 154(15) cm −1, 252(4) cm −1 and 384(18) cm −1, respectively, revealing a significant improvement in performance across the series. The magnetic properties are interpreted with the aid of ab initio calculations, which show substantial increases in the axiality of the crystal field from 1 to 2 to 3 as a consequence of the increasingly dominant role of the Fv tttt and Cp* ligands, with the barrier height and hysteresis properties being attenuated by the equatorial borohydride ligands. The experimental and theoretical results described in this study furnish a blueprint for the design and synthesis of poly-cationic dysprosocenium SMMs with properties that may surpass those of benchmark systems.